PENATALAKSANAAN FISIOTERAPI PADA KONDISI LOW BACK PAIN SPONDILOSIS LUMBAL DENGAN MODALITAS TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION DAN WILLIAM FLEKSI EXERCISE DI RSUD BENDAN KOTA PEKALONGAN - Martharina Friska Pasha; Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Low back pain is a syndrome characterized by major symptoms of pain or a feeling of discomfort in the lower back region and the surrounding bone. Spondyloarthropathy derived from the Greek word for spine. Lumbar spondylosis may  imply changes  in  the spinal  joints,  characterized  by increasing degeneration of the intervertebral discfollowed by changes in bone and soft tissue, or it can mean an  overgrowth  of bone (osteophytes), which  are  mainly located in the  anterior  aspect, lateral, and posterior sometimes from the  edge  of  the superior  and  inferior vertebrae centralis (corpus).To provide an  effective and efficient treatment, then performed a physiotherapy management. Implementation includes any action that checks physiotherapy pain with Sekala Five Story, spasme examination by palpation, examination by range  of  motion with the  midline, and checks the value of muscle strength with Manual MuscleTesting (MMT).In this  case to overcome the  problems  above can be used modality Transcutaneous Electrical Nerve Stimulation in the form of William Flexes And Exercise. After therapy six times, in getting results in a  decrease  in tenderness, and pain of  motion, increase muscle  strength  in  the trunk region, and increase range  of  motion in  the trunk region. Evaluation on the  sixth therapy for functional activity using oswestryability disability index showed an increase infunctional activity.Keywords : Low  Back Pain Spondilosis  Lumbal, Transcutaneous Electrical Nerve Stimulation and William Flexion Exercise.